Acute effects of static stretching exercises on shortdistance flutter kicking time in child swimmers - (:unkn) unknown (Centre for Performance Analysis, 2012)
The aim of this study was to determine the effects of static stretching exercises and gender on the kickboard flutter kicking swimming times of 11- to 12-year-old swimmers. Twenty-nine (15 boys and 14 girls) competitive swimmers performed short-distance (25 m and 50 m) flutter kicking swims with a kickboard under both unstretched and stretched conditions on separate days. The conditions were randomly assigned to the participants. In total, 4 static stretching exercises (3 active and 1 passive) were applied to the lower extremities (2 x 30 s; 10 s rest). The results indicated that 25 m (girls: 22.72 ± 2.60 s, 22.54 ± 2.26 s; respectively; boys: 23.35 ± 3.85 s, 22.69 ± 3.77 s; respectively) and 50-m (girls: 51.40 ± 6.04 s, 50.23 ± 5.93 s; respectively; boys: 50.38 ± 6.80 s, 49.30 ± 6.56 s; respectively) distances flutter kicking swim times were not significantly different between no stretch and the stretch conditions or between boys and girls (P > 0.05) According to these findings, and contrary to the results of certain studies of land performance, the static stretching exercises did not have any effect on the kickboard flutter kicking swimming time and did not result in any difference in performance level between genders.
Keywords: Kickboard; Lower extremity; Stretched; Swimming; Unstretched